Theory of mind and the triad of perspectives on autism and Asperger syndrome : a view from the bridge - Bogdashina, Olga (Jessica Kingsley Publishers, 2006)
Inspired by the often uncomfortable interplay between autistic individuals, parents and professionals in understanding autistic spectrum conditions, Olga Bogdashina uses the concept of Theory of Mind (ToM) to consider these groups' different (and often conflicting) perspectives. ToM is the ability to imagine and make judgements about what others feel and think; its absence in autistic individuals is called 'mindblindness'. This book addresses the 'mindblindness' of people united in their interest in autism but divided by their different angles and perspectives. Divided into four parts, the book first defines autism, then the views of the three main groups working with it - autistic individuals, parents and professionals - under the headings of classifications, diagnosis, causes, development, theories and treatment. By comparing and reconciling the different perspectives in this way, the book helps each group to understand and predict each other's responses and behaviours. This enlightening and innovative book offers a unique way of 'stepping in each other's shoes' and is a valuable resource for all people living or working with autism.